1977
DOI: 10.1115/1.3453244
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Analysis of Capillary Compensated Hydrostatic Journal Bearings by Finite Element Method

Abstract: Using finite element method steady state and dynamic performance of a capillary compensated hydrostatic journal bearing have been investigated. For stability studies, the critical mass of the bearing system has been determined by Routh’s criterion. The locus of the journal center has been predicted by discretizing time and numerically integrating the equations of motion governing the journal bearing system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Stout et al 1,2 concluded that non-recessed journal bearings are best suited for high-speed applications and to minimize power dissipation. Singh et al 3 investigated the steady-state and dynamic performance characteristics of capillary compensated hydrostatic journal bearings using finite element methods. Detailed studies by Rowe and co-workers 4-8 concerning journal bearings focused significant attention on various issues.…”
Section: Non-dimensional Parametersmentioning
confidence: 99%
“…Stout et al 1,2 concluded that non-recessed journal bearings are best suited for high-speed applications and to minimize power dissipation. Singh et al 3 investigated the steady-state and dynamic performance characteristics of capillary compensated hydrostatic journal bearings using finite element methods. Detailed studies by Rowe and co-workers 4-8 concerning journal bearings focused significant attention on various issues.…”
Section: Non-dimensional Parametersmentioning
confidence: 99%
“…Rowe et al outlined a procedure to optimize the design parameters of multi-recess hydrostatic bearings based on minimum power consumption; they suggested an optimal ratio of the land part to recess of 0.25 [9]. Singh et al calculated the dynamic coefficients of capillary-compensated bearings in a pure hydrostatic operation [10]. Ghosh calculated the stiffness and damping coefficients of pure hydrostatic operation according to changes in recess pressure ratio and eccentricity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Stout and Rowe (1974a, b) reported that non‐recessed journal bearings are best suited for high‐speed applications and to minimize power dissipation. Rowe and Koshal (1977, 1979) optimized the hybrid journal bearings, which involve the comparison of the bearings to be optimized with a reference bearing on the basis of load/total power, load/pumping power and load/flow (Singh et al , 1977). Rowe et al (1982) concluded that the hole‐entry bearings are particularly effective when compared slot‐entry as well as recessed bearings for better load support and low‐energy consumptions at zero as well as for high‐speed operations.…”
Section: Introductionmentioning
confidence: 99%